Depression after status epilepticus: behavioural and biochemical deficits and effects of fluoxetine - Mazarati, Andréy (Oxford University Press, 2008)
Depression represents one of the most common comorbidities in patients with epilepsy. However, the mechanisms of depression in epilepsy patients are poorly understood. Establishment of animal models of this comorbidity is critical for both understanding the mechanisms of the condition, and for preclinical development of effective therapies. The current study examined whether a commonly used animal model of temporal lobe epilepsy (TLE) is characterized by behavioural and biochemical alterations involved in depression. Male Wistar rats were subjected to LiCl and pilocarpine status epilepticus (SE). The development of chronic epileptic state was confirmed by the presence of spontaneous seizures and by enhanced brain excitability. Post-SE animals exhibited increase in immobility time under conditions of forced swim test (FST) which was indicative of despair-like state, and loss of taste preference in saccharin solution consumption test which pointed to the symptomatic equivalence of anhedonia. Biochemical studies revealed compromised serotonergic transmission in the raphe-hippocampal serotonergic pathway: decrease of serotonin (5-HT) concentration and turnover in the hippocampus, measured by high performance liquid chromatography, and decrease of 5-HT release from the hippocampus in response to raphe stimulation, measured by fast cyclic voltammetry. Administration of fluoxetine (FLX, 20 mg/kg/day for 10 days) to naive animals significantly shortened immobility time under conditions of FST, and inhibited 5-HT turnover in the hippocampus. In post-SE rats FLX treatment led to a further decrease of hippocampal 5-HT turnover; however, performance in FST was not improved. At the same time, FLX reversed SE-induced increase in brain excitability. In summary, our studies provide initial evidence that post-SE model of TLE might serve as a model of the comorbidity of epilepsy and depression. The finding that behavioural equivalents of depression were resistant to an antidepressant medication suggested that depression in epilepsy might have distinct underlying mechanisms beyond alterations in serotonergic pathways.